Secrets of the tide : tide and tidal current analysis and applications, storm surges and sea level trends - Boon, John D. (Horwood Pub., 2004)
This postgraduate level text and reference treatise introduces readers to tides, tidal currents, storm-surges and sea level trends in coastal regions. The book is based on tidal waters of Maryland, Virginia, Chesapeake Bay and the Atlantic regions known to the author, and also provides international examples from the UK and different locations around the world, which allows readers to compare and contrast tidal regimes and to perform tidal analysis from data in their own environment. It is an important book for teachers, researchers, planners and engineers responsible for coastal defences as well as new infrastructure and waterway modification in ports and harbours. The wealth of informative detail and data provided makes this text worthwhile for readers who need a wider understanding of this increasingly important topic for coastal zone residents. MATLAB scientific programming language, simple-to-use Graphical User Interface (GUI) programs are introduced for students, researchers and engineering consultants, available at no cost from MATLAB Central file exchange (http://www mathworks.com/matlabcentral). GUI programs provide the tools for analysing water level or water current observations, deriving the major tidal constituents, and showing first hand how tide and tidal current predictions are made in addition to producing unrivalled colour graphic visualisations. GUI is the author's tidal analysis and is particularly suited for the investigation of storm surge in coastal waters. Professor Boon has studied tidal behaviour in world coastal zones and here assembles information for public and private use from his capacity as advisor to state and federal authorities and corporate organisations. Introduces tides, tidal currents, storm-surges and sea level trends in coastal regionsProvides examples from the US, the Atlantic, the UK and different locations around the worldMATLAB scientific programming language and simple-to-use Graphical User Interface (GUI) programs are introduced for students, researchers and engineering consultants.